Prevalence of Anemia in Iraqi Children (Eurasian Medical Research Periodical, 2022)
A demographic survey was conducted in Wasit Governorate, Iraq, where 45 children were collected from Al-kut Hospital for Gynecology and Obstetrics, Wasit, Iraq. Our study was limited to children between the ages of 10 months to 45 months. This paper aims to investigate and know the Prevalence of Anemia in Iraqi Children and the evaluation stages were adopted to the exclusionary studies to confirm the anemic children by relying on the statistical analysis program spss soft, the MEAN SD was found to the patients' ages of 28.04 ± 8.82, and the patients were divided to 30 boys and 15 girls. It was concluded from this study that anemia has a significant impact on children as it depends on several determinants, including the type of breastfeeding in addition to iron supplementation and other important factors